Potensi Dan Peran Zakat Terhadap Peningkatan Kesejahteraan Usaha Mikro Kecil Menengah (Studi Kasus terhadap Balai Bina Mandiri Medan Denai) - Nadra Khalizah Siregar; Muhammad Yafiz; Rahmi Syahriza (Universitas Maritim AMNI Semarang, 2023)
Balai Bina Mandiri Denai is a Micro, Small and Medium Enterprise (UMKM) as one of the programs to realize Zakat funds originating from the Medan Zakat House. This program is the embodimentSmile Mandiri, which is a local-based economic empowerment program for underprivileged communities with the aim of reducing poverty through entrepreneurship. The purpose of the research on Balai Bina Mandiri Medan Denai is to find out how the Potential and Role of Zakat on MSMEs at Balai Bina Mandiri Medan Denai is. This research was conducted using descriptive qualitative research by the researcher, which is expected to be able to determine the potential and role of the Zakat Fund on the welfare of MSMEs at Balai Bina Mandiri Medan Denai. From the results obtained by the researchers, the potential that comes from Rumah Zakat itself is very promising for the MSMEs of the Medan Denai Center for Mandiri Development. And the role of Zakat in the Bina Mandiri Medan Denai hall is very instrumental to them. They can get a profit of Rp. 350,000.00, - up to Rp. 500.000,00,-. per day. With a variety of products sold..Based on research results show that with the Mandiri Smile Program from Rumah Zakat, and with the establishment of Balai Bina Mandiri Denai, it plays a very big role in providing additional funds to meet their household needs.